2004
DOI: 10.1183/09031936.03.00025403
|View full text |Cite
|
Sign up to set email alerts
|

Stretch-induced changes in constricted lung parenchymal strips: role of extracellular matrix

Abstract: Stretch-induced changes in constricted lung parenchymal strips: role of extracellular matrix. F.G. Salerno, A. Fust, M.S. Ludwig. #ERS Journals Ltd 2004. ABSTRACT: Large amplitude oscillations of contracted airway smooth muscle cause relative relaxation of the preparation. However, little is known about the effect of mechanical stretch on distal lung behaviour.Rat parenchymal strips were suspended in an organ bath and attached at one end to a force transducer and at the other end to a servo-controlled lever ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Thus, a reduction in regional lung compliance and a redirectioning of blood Xow and ventilation away from these regions would ensue (Oldmixon et al 2001). Deep breaths cannot reverse pneumoconstriction, but lung parenchyma stretching reduces the elastance possibly by changing the ultrastructural arrangement of the connective tissue matrix (Salerno et al 2004). In this context, the normalization of dynamic compliance after DB reported herein could be explained.…”
Section: Discussionmentioning
confidence: 78%
“…Thus, a reduction in regional lung compliance and a redirectioning of blood Xow and ventilation away from these regions would ensue (Oldmixon et al 2001). Deep breaths cannot reverse pneumoconstriction, but lung parenchyma stretching reduces the elastance possibly by changing the ultrastructural arrangement of the connective tissue matrix (Salerno et al 2004). In this context, the normalization of dynamic compliance after DB reported herein could be explained.…”
Section: Discussionmentioning
confidence: 78%
“…When isolated lung tissue is exposed in vitro to elastase, an enzyme that digests elastin and collagen disrupting the three-dimensional network of fibres that compose the architecture of the tissue, lung compliance increases [4]. The extracellular matrix is also responsible for a large part of the lung tissue hysteretic properties, and of the energy dissipation occurring during breathing accounted for by lung tissue resistance [5].…”
Section: The Extracellular Matrix and The Mechanical Properties Of The Lungmentioning
confidence: 99%
“…Indeed, it has been demonstrated that it is a shortening velocity rather than force generation per unit of muscle mass that is related to bronchial hyperresponsivenss [10]. Another mechanism, possibly relating extracellular matrix and asthma, is the ability of lung volume excursions to relax airway smooth muscle and decrease lung elastance [5].…”
Section: Extracellular Matrix and Asthmamentioning
confidence: 99%
“…In response to different ECM components, such as fibronectin, collagen and perlecan, the proliferation, survival and inflammatory mediator release from smooth muscle cells can be altered 8083. Lung cells also possess the ability to modulate the surrounding ECM in response to factors such as physical stress and soluble mediators 77,84,85. Moreover, we have previously shown that the ECM produced by asthmatic cells can induce cells from non-asthmatic subjects to assume the characteristics of those from asthmatic subjects 77…”
Section: The Etiology Of Remodelingmentioning
confidence: 99%